Peran Asisten Produksi Terhadap Kualitas Tayangan Pada Program Showbiz Metro TV - Jakarta - Rizkia Aulia Putri (Asosiasi Ide Bahasa Kepri, 2026)
This study examines the strategic role of a Production Assistant in supporting the smooth running and quality of a television program. Showbiz Metro TV, an infotainment program that prioritizes consistency in maintaining content quality, accuracy, and audiovisual quality, requires optimal production coordination, one of which is through the role of the production assistant. The research method used was a qualitative method with a descriptive approach. Data collection techniques were conducted through direct field observations during production, in-depth interviews, and documentation of visual materials involving the production assistant and the relevant production team. The results indicate that production assistants play a crucial role in the pre-production, production, and post-production stages, from scheduling and crew coordination to technical preparation, to ensuring the smooth running of the production process in the field. This role directly contributes to broadcast quality, particularly in aspects of timeliness, completeness of material, and technical smoothness of broadcasts. Therefore, it can be concluded that production assistants play a significant role in maintaining and improving the broadcast quality of Showbiz Metro TV Jakarta.